ALIH KODE DALAM KOMUNITAS BACKPACKER DI FACEBOOK - RORY, STELLA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research design entitled â€œCode Switching In Backpacker Community in Facebookâ€ is an attempt to identify, analyze, and find the reason of code switching phenomena in backpacker community. The theory used in this researchareby Hoffman and Fishman and this research appliesadespcriptive method. The result of this research showsÂ that there are two kinds of code switching, intra-sentensial switching and inter-sentensial switching. The reasons of the happening of the code switching in Backpacker community are through its speaker, listener or opponent speakerâ€™s sayings, changing situation of the presence of the third person, the formalchangesinto informal ones, change of subject, and itsprestige. Keywords :Sociolinguistics, Code switching, Facebook, Backpacker Â